2019
DOI: 10.1371/journal.pntd.0007383
|View full text |Cite
|
Sign up to set email alerts
|

Hindgut microbiota in laboratory-reared and wild Triatoma infestans

Abstract: Triatomine vectors transmit Trypanosoma cruzi , the etiological agent of Chagas disease in humans. Transmission to humans typically occurs when contaminated triatomine feces come in contact with the bite site or mucosal membranes. In the Southern Cone of South America, where the highest burden of disease exists, Triatoma infestans is the principal vector for T . cruzi . Recent studies of other vector-borne illnesses hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 69 publications
(146 reference statements)
10
63
4
Order By: Relevance
“…Similar findings are reported for two species of North American Triatoma, in which the authors further conclude that T. cruzi infection leads to apparent increases in bacterial diversity within the triatomine host gut (Rodríguez-Ruano et al, 2018). The finding of increased bacterial diversity in the hindgut of T. cruzi-infected triatomines is consistent with previously reported changes in the gut microbiome and host physiology upon T. cruzi infection in South American triatomines (Vieira et al, 2015;Díaz et al, 2016), though another study found no impact of T. cruzi infection on alpha diversity metrics in both lab-reared and wild triatomine individuals (Waltmann et al, 2019). These studies point to the potential shaping of the triatomine gut microbial population by T. cruzi during infection but also the dynamic nature of the hindgut community that may be governed by a variety of factors including interspecies variation, collection location, sex, life cycle stage, and wild versus lab-reared populations.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Similar findings are reported for two species of North American Triatoma, in which the authors further conclude that T. cruzi infection leads to apparent increases in bacterial diversity within the triatomine host gut (Rodríguez-Ruano et al, 2018). The finding of increased bacterial diversity in the hindgut of T. cruzi-infected triatomines is consistent with previously reported changes in the gut microbiome and host physiology upon T. cruzi infection in South American triatomines (Vieira et al, 2015;Díaz et al, 2016), though another study found no impact of T. cruzi infection on alpha diversity metrics in both lab-reared and wild triatomine individuals (Waltmann et al, 2019). These studies point to the potential shaping of the triatomine gut microbial population by T. cruzi during infection but also the dynamic nature of the hindgut community that may be governed by a variety of factors including interspecies variation, collection location, sex, life cycle stage, and wild versus lab-reared populations.…”
Section: Introductionsupporting
confidence: 86%
“…If there are microbial targets living in the hindgut of triatomines that may be effective for T. cruzi control, the relative impact of transient microbes on the interpretation of these communities must be verified. Despite the potential impact of transient microbes in the interpretation of overall diversity, we found a pattern of differential abundance of specific bacterial groups in T. cruzipositive and T. cruzi-negative individuals, one of which (i.e., members of the Porphyromonadacea family -in the current study represented by Petrimonas) has been previously reported as enriched in T. cruzi-positive members of Triatoma infestans collected from Peru (Waltmann et al, 2019). This result motivates further investigation of diverse species of triatomine insects to clarify the relationship between specific bacterial taxa and the T. cruzi parasite.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations